A comparative study of RIPASA score and modified Alvarado score in diagnosis of acute appendicitis - El Sherpiny, Waleed Yusif (International Surgery Journal, 2019)
Background: Various diagnostic criteria have been described for diagnosing acute appendicitis. Of these, Alvarado score has been the most commonly used. The RIPASA score is a new diagnostic scoring system developed for the diagnosis of acute appendicitis and showed higher sensitivity, specificity and diagnostic accuracy as compared to Alvarado score. we want to compare prospectively Alvarado and RIPASA score by applying them to patients attending emergency department complaining of right iliac fossa pain that could probably be acute appendicitis. Methods: Patients with clinically suspected acute appendicitis were classified according to both Alvarado and RIPASA scoring systems before undergoing surgery. Histopathological examination of the removed appendix was taken as the gold standard for diagnosis of acute appendicitis. Results: Among (90%) patients had histologically confirmed appendicitis. With the cut-off value greater than 7.5 for RIPASA score; sensitivity, specificity, positive predictive value, negative predictive value, diagnostic accuracy were 88.2%, 14.5%, 73.1%, 32%,and 68% respectively. With the cut-off value greater than 7 for Alvarado score, sensitivity, specificity, positive predictive value, negative predictive value, diagnostic accuracy and negative appendectomy rates were 51.2%, 80 %, 91 %, 29%, and 57%, respectively. 87.5% of patients were correctly stratified by RIPASA under higher probability group while only 45% were classified by Alvarado as high probability. Conclusions: RIPASA scoring system showed high sensitivity and diagnostic accuracy in comparison to Alvarado scoring system. So, it can be applied for the diagnosis of acute appendicitis.